Development of fatigue detection technique using photoplethysmogram signal - Sidek, Khairul Azami; Haron, Nur Syamim Izzatie; Mansor, Hasmah (Malaysia Technical Scientist Association, 2019)
Fatigue is a subjective feeling of tiredness which has physical or mental implications. Thus, in this study we will prove the robustness and reliability of PPG signals as a fatigue detection mechanism. Undeniably, PPG signals have the superior crite-ria which are non-invasive, small in size, low power consumption as well as low in cost. A total of five different respondents have been assigned to perform the skipping exercise and running in place in a non-stop duration of 5 minutes. These PPG signals undergo a two- stage filter and amplifier to clean and boost the signals. Then, discriminative features were extracted from the PPG morphology. Finally, these samples were classified using five types of classification parameters which are peak to peak interval, pulse interval, ΔT calculation, heart rate and respiratory rate. The experimental results demonstrated that the proposed method of detecting fatigue using PPG signals has great potentials where each PPG signal shows a differ-ent pattern of complete cycle between one conditions to the other which suggest fatigue detection using PPG signal is possi-ble. The increase in the number of complete cycle in the data collected happened because of the frequency of the PPG signal when performing fast activity. This led to the decrease in the time duration for peak to peak interval, pulse interval and ΔT calculation. Thus, the difference in time duration is capable of distinguishing between fatigue and normal conditions. The results also showed that the heart rate and respiratory rate increases when performing either running or skipping activity.